Pengaruh Gaya Kepemimpinan, Kompensasi, dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja Karyawan - Variandi, Ivan; Oh, Andi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study to determine the effect of leadership style, compensation and job characteristics on job satisfaction at CV Anugrah Manggala Jaya. The type of research used in this study is quantitative research. The data in this study uses primary data using research data collection techniques and questionnaires, as well as secondary data by collecting documents related to research problems. The sample in this study were 35 respondents. The sampling technique in this study used the census method. Data analysis using descriptive quantitative with multiple linear regression test analysis model, hypothesis testing using test coefficient of determination (R²) and partial test (t test). The results showed that based on the Partial Test (t test), the leadership style partially did not significantly influence CV Anugrah Manggala Jaya’s job satisfaction, while compensation and job characteristics significantly affected CV Anugrah Manggala Jaya’s job satisfaction. Predictive ability of the three variables on Job Satisfaction of 57.4% is indicated by the magnitude of adjusted R square, while the remaining 42.6% is influenced by other variables not examined.